2011
DOI: 10.5051/jpis.2011.41.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of globular adiponectin on interleukin-6 and interleukin-8 expression in periodontal ligament and gingival fibroblasts

Abstract: PurposeGlobular adiponectin (gAd) is a type of adipocytokine, which is mainly produced by adipose tissue. It has been reported that gAd acts as a pro- as well as an anti-inflammatory factor. Interleukin (IL)-6 and IL-8 are pro-inflammatory cytokines. To investigate the role of gAd on periodontal tissues, the expression of adiponectin receptor 1 (AdipoR1) and the effect of gAd on the expression of IL-6 and IL-8 were investigated in periodontal ligament (PDL) and gingival fibroblasts.MethodsPDL and gingival fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
2
1
1
Order By: Relevance
“…Although these adipokines could also be detected by real-time PCR, their expressions were very slight and barely modulated. A few studies have reported that HGF express AdipoR1 and AdipoR2, but not adiponectin, which seems to be in contrast to our findings [ 28 , 29 ]. However, in these studies, the expression of adiponectin was analyzed by end-point PCR and immunoblotting, but not real-time PCR, which is a highly sensitive and quantitative assay.…”
Section: Discussioncontrasting
confidence: 99%
“…Although these adipokines could also be detected by real-time PCR, their expressions were very slight and barely modulated. A few studies have reported that HGF express AdipoR1 and AdipoR2, but not adiponectin, which seems to be in contrast to our findings [ 28 , 29 ]. However, in these studies, the expression of adiponectin was analyzed by end-point PCR and immunoblotting, but not real-time PCR, which is a highly sensitive and quantitative assay.…”
Section: Discussioncontrasting
confidence: 99%
“…As previously reported, AdipoR1 and AdipoR2 are expressed in PDL cells [65, 71, 72]. Our experiments confirm the expression of both adiponectin receptors in PDL cells.…”
Section: Discussionsupporting
confidence: 92%
“…Another novel finding of our study is the observation that adiponectin is expressed in PDL cells and that it exerts an autostimulatory effect on its expression. As previously reported, AdipoR1 and AdipoR2 are expressed in PDL cells [ 65 , 71 , 72 ]. Our experiments confirm the expression of both adiponectin receptors in PDL cells.…”
Section: Discussionsupporting
confidence: 70%
“…However, a study in human gingival keratinocytes (GK) found no effect of total adiponectin alone on cell proliferation and an inhibitive effect in combination with P. gingivalis LPS (Kraus et al, 2012). Likewise, in separate studies, neither MMP-1, IL-6 nor IL-8 protein expression was affected by total or globular adiponectin in human GK, gingival fibroblasts (GF) or PDL cells (Iwayama et al, 2012;Kraus et al, 2012;Park et al, 2011). Yet, combined stimulation of human GK with P. gingivalis LPS and adiponectin, or of GFs with IL-1β and adiponectin, resulted in decreased IL-6 and IL-8 protein expression compared to IL-1β /LPS stimulation alone (Iwayama et al, 2012;Kraus et al, 2012).…”
Section: Strengths and Limitationsmentioning
confidence: 99%